Grindability and combustion behavior of coal and torrefied biomass blends. (September 2015) - Gil, M.V.; García, R.; Pevida, C.; Rubiera, F.
Highlights: Biomass was treated by torrefaction before its co-combustion with coal. Biomass grindability was assessed from the particle size distribution after grinding. Torrefaction increased the proportion of small size fractions after grinding. Chestnut woodchips torrefied at 280 °C showed the best grindability characteristics. The addition of torrefied biomass reduced NO and SO2 emissions during co-combustion. Abstract: Biomass samples (pine, black poplar and chestnut woodchips) were torrefied to improve their grindability before being combusted in blends with coal. Torrefaction temperatures between 240 and 300 °C and residence times between 11 and 43 min were studied. The grindability of the torrefied biomass, evaluated from the particle size distribution of the ground sample, significantly improved compared to raw biomass. Higher temperatures increased the proportion of smaller-sized particles after grinding. Torrefied chestnut woodchips (280 °C, 22 min) showed the best grinding properties. This sample was blended with coal (5–55 wt.% biomass). The addition of torrefied biomass to coal up to 15 wt.% did not significantly increase the proportion of large-sized particles after grinding. No relevant differences in the burnout value were detected between the coal and coal/torrefied biomass blends due to the high reactivity of the coal. NO and SO2 emissions decreased as the percentage of torrefied biomass in the blend with coal increased.